2021
DOI: 10.1128/mcb.00594-20
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Landscapes of Noncoding RNAs Regulating VEGFA and VEGFC Expression in Endothelial Cells

Abstract: Vascular endothelial growth factors (VEGFs) are best known as key regulators of angiogenesis and lymphangiogenesis. Although VEGFs have been promising therapeutic targets for various cardiovascular related diseases, their regulatory landscape in endothelial cells remains elusive. Several studies have highlighted the involvement of non-coding RNAs (ncRNAs) in the modulation of VEGF expression. In this study, we investigated the role of two classes of non-coding RNAs, long ncRNA (lncRNA) and enhancer RNAs (eRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 125 publications
(139 reference statements)
1
11
0
Order By: Relevance
“…However, super-enhancers hierarchical organization does not exclude contribution of some or all enhancers within a SE, and as such it was demonstrated that combinatorial deletion of enhancers within a SE led to a greater effect on gene expression ( 66 , 69 ). This collaborative activity of enhancers within a SE is also reflected in our data from the enhancer deletions, whereby deletion of either enhancer resulted in similar gene regulation of approximately 2000 genes, in the range reported in previous enhancer deletion studies ( 70 , 71 ). Thus, the close overlap of differentially regulated genes would indicate that most of the enhancer activity is related to the SE activity as a whole, and perturbation of any enhancer within the cluster may negatively affect the SE activity.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, super-enhancers hierarchical organization does not exclude contribution of some or all enhancers within a SE, and as such it was demonstrated that combinatorial deletion of enhancers within a SE led to a greater effect on gene expression ( 66 , 69 ). This collaborative activity of enhancers within a SE is also reflected in our data from the enhancer deletions, whereby deletion of either enhancer resulted in similar gene regulation of approximately 2000 genes, in the range reported in previous enhancer deletion studies ( 70 , 71 ). Thus, the close overlap of differentially regulated genes would indicate that most of the enhancer activity is related to the SE activity as a whole, and perturbation of any enhancer within the cluster may negatively affect the SE activity.…”
Section: Discussionsupporting
confidence: 84%
“…We have recently observed a similar discrepancy between in vitro reporter assays and genomic deletion of enhancers. However, in this case enhancers showed activity in vitro but not following CRISPR/Cas9 deletion ( 71 ). What is clear is that in vitro assays alone are insufficient to analyse enhancer activity, and multiple approaches are required to adequately investigate these regulatory regions.…”
Section: Discussionmentioning
confidence: 96%
“…The recent studies showed that non-immune inflammatory cells have inflammatory changes and altered cellular states under eRNA regulation ( 135 138 ). Isidore et al ( 136 ) found that VEGFA-eRNA5 and VEGFC-eRNA3 in endothelial cells affect angiogenesis and lymphangiogenesis by regulating endogenous transcription and VEGFA and VEGFC expression. Additionally, eRNAs were found to be well correlated with VEGF expression across cell types and in response to hypoxic stimuli using GRO-Seq.…”
Section: Resultsmentioning
confidence: 99%
“…Local transferring of certain genes has been verified to be effective in inhibiting neointimal hyperplasia and neoatherosclerosis. These genes include Inducible NOS (iNOS) (157), vascular endothelial growth factor (VEGF) (158), tissue inhibitor of metalloproteinase 1 (TIMP-1) (159), monocyte chemoattractant protein-1(MCP-1) (160), Ras mutation (161), TGF-β1 receptor Type II (TβRII) (162). iNOS is rarely expressed under physiological conditions but highly expressed under inflammatory stimuli.…”
Section: Gene Therapy and In-stent Restenosismentioning
confidence: 99%